A prospective population-based study of preterm pre-labour rupture of membranes between 24 and 34 weeks of gestation in Cape Town Metro East: measuring protocol intervention fidelity and clinical outcome - Mbungu, N. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.